UPAYA MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPS MELALUI PEMBELAJARAN KOOPERATIF TARI BAMBU - Alfi Syukriyati (Ideguru: Jurnal Karya Ilmiah Guru, 2017)
The problems that exist in the IPS study include lack of students’ interest toward this subject, many materials involved and the low level of students learning outcomes. The main and urgent problem to be solved in this IPS study is the low level of students learning outcomes. This research aims to improve students learning outcomes in IPS study through bamboo dance as one of the types in Cooperative learning. This research was conducted on the students of IX C SMP 3 Imogiri in 2016 / 2017 academic Year, involving 24 students. This research is a classroom action research that conducted in four meetings within two cycles, and focused on improving students learning outcomes in each cycle. The steps run in this research include: planning, action, reflection/evaluation and follow up. The data in students learning outcomes includes the result of students competence evaluation in achieving Minimum Passing Grade Criteria and the students’ activeness level. The result if this research was the improvement of students’ learning outcomes based on the Minimum Passing Grade Criteria. It showed that the result of Post test in the first meeting in Cycle 1 is 62.50% and improved to 87.50% in the second meeting in the same cycle, and in the first meeting of cycle 2 improved to 91.30% and 87.50% in the second meeting of cycle 2. The result of students’ competence evaluation in the end of cycle 1 is 91.66% and 91.66% in the end of cycle 2. The observation sheet showed that the level of students’ activeness in the first meeting of cycle 1 is 83.33% and improved to 87.50% in the second meeting of cycle 1, and improved to 100% in the first and second meetings of cycle 2.